Associations between obesity and overweight and fall risk, health status and quality of life in older people - Rebecca J. Mitchell; Stephen R. Lord; Lara A. Harvey; Jacqueline C.T. Close (Elsevier, 2014)
Abstract Objectives: To determine whether overweight and obese individuals have higher reported fall and fall injury risk than individuals of healthy weight, and to examine the influence of BMI on health, quality of life and lifestyle characteristics of fallers. Methods: A representative sample of community‐based individuals aged 65 years and older in New South Wales was surveyed regarding their history of falls, height, weight, lifestyle and general health within a 12‐month period. Results: Obese individuals had a 31% higher risk of having fallen, but no higher risk of a fall‐related injury compared to healthy‐weight individuals. Obese fallers also had a 57% higher risk of believing nothing could be done to prevent falls; a 41% higher risk of using four or more medications; a 30% higher risk of experiencing moderate or extreme pain or discomfort; were 26% less likely have walked for two or more hours in the last week; and were less likely to think they were doing enough physical activity. Conclusions: Older obese individuals have an increased risk of falls and obese fallers have a higher prevalence of pain and inactivity than fallers of a healthy weight. Implications: A decrease in sedentary lifestyle and regular weight‐bearing exercise may reduce fall risk in older obese individuals.